MOLECULAR CHARACTERIZATION OF MEASLES VIRUS IN CHILDREN WITH FEVER AND MACULOPAPULAR RASH IN SOUTH WESTERN NIGERIA (2014)
The use of live attenuated vaccines for measles has considerably reduced the incidence of the disease worldwide. However, measles remains endemic and a major cause of under-five morbidity and mortality in many developing countries. Molecular characterization of wild-type measles virus is a key component to laboratory surveillance activities in all phases of measles control. This study was therefore designed to carry out molecular characterization of measles virus strains circulating in south-western Nigeria. Blood and throat swab samples were collected over a period of five years (2007-2011) from 1200 children (639 females and 561 males) aged six months to five years presenting with fever and maculopapular rash. The participants were consecutively recruited from Ibadan (Adeoyo General and Oni Memorial Children Hospitals) and Lagos (Isolo General and Massey Street Children Hospitals). All the samples were tested for the presence of IgM antibodies against measles virus, rubella virus and parvovirus B19 using Enzyme-Linked Immunosorbent Assay. Viral RNA were extracted from 286 throat swabs and transcribed to cDNA by reverse transcription using random hexamers. The cDNA was then amplified using a nested PCR and the amplicons directly sequenced in both forward and reverse directions. The virus sequences were edited and analysed for phylogenetic relationships by clustalW and maximum likelihood methods using specialised software based on their nucleotide and amino acid sequences. Data were analysed using descriptive statistics and ANOVA at P=0.05 One hundred and twenty eight (10.7%) children tested positive for measles IgM antibodies. The prevalence of measles infection was higher in female (11.58%) than in male (9.62%) participants though the difference was not significant (p=0.08). The rate of detection of measles virus was relatively constant (10.3%-11.9%) over the five year period. Rubella virus IgM antibodies were detected in 267 (24.7%) children, (151 females and 116 males) while parvovirus B19 IgM antibodies were found in 96 (11.9%) children (51 females and 45 males). Twenty three (8.1%) of the 285 swabs processed were positive for measles by PCR out of which the target region was successfully sequenced from 11 of them. Ten of the sequenced strains were classified as genotype B3 cluster 1 while one showed high sequence similarity with measles virus of clade A. Detection and isolation of measles virus of clade A in Nigeria was described for the first time and showed wider circulation of the clade outside of its previous regions of detection in Europe and Americas. Measles virus of genotype B3 cluster 1 is the predominant circulating strain in Southwestern Nigeria. There was uninterrupted transmission of endemic virus in the study areas.